Opportunities for implementing digital applications to monitor the impact of risk-minimization measures within the pharmacovigilance process: Scoping review of published literature - Ilko Getov; Denitsa Panayotova; Stanimir Dobrev; Maria Dimitrova; Valentina Petkova (Pharmacia)
The study provides an overview of innovative digital solutions to meet the evolving needs of drug safety monitoring and improve patient outcomes, focusing on implementing digital applications to enhance the monitoring of additional risk-minimization measures (aRMMs) for pharmacovigilance. Over the last decade, the literature has highlighted a critical unmet need for improving the efficiency and accuracy of adverse event reporting. This is crucial for identifying risks not observed during clinical trials. Digital tools offer potential benefits by providing real-time reporting, comprehensive safety data, and increased patient engagement, thus addressing the challenges of underreporting and incomplete data in pharmacovigilance. The scoping review of the literature identified current global practices and evaluated the feasibility of adopting such solutions locally. The findings suggest digital tools such as mobile applications, web-based platforms, and electronic health record integrations are effective mechanisms for the collection of real-world data, patient-reported outcomes, and patient engagement in terms of drug safety surveillance. These tools address significant challenges inherent in traditional systems, such as underreporting and data fragmentation. Integrating digital solutions into pharmacovigilance can significantly enhance the timeliness and reliability of drug safety data, supporting more informed regulatory decision-making and ultimately improving patient outcomes.